LEGAL GUARANTEES OF THE USE OF THE INTERNET BY INDIVIDUALS - Kudratillaev Jakhongir (Scholar Express Journals, 2023)
This article is devoted to the legal analysis of the constitutional legal basis of the right to use the Internet. The role of the Internet in the modern world and the level of freedom of access to the Internet in different countries are compared and analyzed. The specific aspects of whether the freedom of access to the Internet should be regulated at the level of the constitution or at the level of the law as a separate personal right have been studied. It is explained that the regulation of relations related to the Internet is required by the time itself and that most of the social relations in the future will be on the Internet. In addition, what is Internet freedom and the right to free access to the Internet are analyzed and explained based on the opinion of scientists. That is, it is justified what conditions should be created by the state for everyone to access the Internet and use it without restrictions.
Keywords: Internet; blogger; constitution; everyone